Model Manajemen Usaha dan Hubungannya dengan Kinerja UKM (Studi Kasus pada UKM Sembung Batik Kulonprogo Jogyakarta) - H Fikriah; Muhaimin; Muhammad Arya Dirgantara (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Indonesian SMEs play an important role in employment and contribution to GDP. However, complex issues still hamper the progress and rise of SMEs. This research aims to explore the causes of these problems by focusing on management models in SMEs. The study uses qualitative methods through interviews, observations, and documentation. The research subject was UKM